2022
DOI: 10.3390/sports10090130
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Free Force-Velocity and Power-Velocity Profiles for Elite Track Sprint Cyclists: The Influence of Duration, Gear Ratio and Pedalling Rates

Abstract: Background: Maximal force-velocity (F/v) profiles for track cyclists are commonly derived from ergometer sprints using an isovelocity or isoinertial approach. Previously, an attempt was made to derive maximal F/v profiles from a single maximal 65-m sprint on the cycling track. Hypothesising that this approach may not accurately reflect the fatigue-free F/v profile, we propose an alternative procedure and compare it to the previous method. Moreover, we test for the impact of gear ratio on diagnostic results. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The gear ratio chosen was 3.87:1 (58/15), corresponding to a deployment of 8.12 m. Pedal force and crank velocity were measured continuously during the warm-up and the race with a power meter (FES, Institute for Research and Development of Sports Equipment, Berlin, Germany) recording the tangential force on the crank with a sampling frequency of 200 Hz and the duration of each crank revolution. This system allows for the creation of sport-specific F/v and P/v profiles [ 6 ]. Raw data was exported and further processed in Office Excel 2016 (Microsoft Corporation, Redmond, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The gear ratio chosen was 3.87:1 (58/15), corresponding to a deployment of 8.12 m. Pedal force and crank velocity were measured continuously during the warm-up and the race with a power meter (FES, Institute for Research and Development of Sports Equipment, Berlin, Germany) recording the tangential force on the crank with a sampling frequency of 200 Hz and the duration of each crank revolution. This system allows for the creation of sport-specific F/v and P/v profiles [ 6 ]. Raw data was exported and further processed in Office Excel 2016 (Microsoft Corporation, Redmond, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that cycling in a standing position can increase power output by 8–12%, which has been attributed to additional power development from the upper body [ 25 , 26 , 27 , 28 ]. To accurately analyse the race data and to calculate the fatigue-induced changes in optimal cadence, separate fatigue-free F/v and P/v profiles were created for a standing and a seated position on the bike, as described in a previous publication [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations